Strategic Accounting Analysis of Value – Revolutionary Phase of Accounting Science’s Development - Trifonov, Trifon (Research Papers, 2005)
Researched in the paper are the essence and the particularities of the strategic accounting management – the modern topic into accounting science’s development. Defined are the differences between operative (current) and strategic analysis, and that last one should not be identified with the long-term accounting research. The activity based costing and accounting budgeting are interpreted as an emanation of strategic management under accounting form. The conclusion is that in accordance with the dialectic laws accounting analysis get back to its basic economic roots of research.